Stem Cells in Pituitary Tumors: Experimental Evidence Supporting Their Existence and Their Role in Tumor Clinical Behavior - Mantovani, Giovanna; Giardino, Elena; Treppiedi, Donatella; Catalano, Rosa; Mangili, Federica; Spada, Anna; Arosio, Maura; Peverelli, Erika (Frontiers in Endocrinology, 2019)
Although generally benign, pituitary tumors frequently show local invasiveness and resistance to pharmacological therapy. After the demonstration of the existence of pituitary gland stem cells, over the past decade, the presence of a stem cell subpopulation in pituitary tumors has been investigated, analogous to the cancer stem cell model developed for malignant tumors. This review recapitulates the experimental evidence supporting the existence of a population of stem-like cells in pituitary tumors, focusing on their potential role in tumor initiation, progression, recurrence and resistance to pharmacological therapy.